Delivery of Polypeptide Drugs Using Nanoparticles Made of Recombinant Spider Silks Derived From MaSp4 Protein - Peng Z; Wen R (International Journal of Nanomedicine)
Zheng Peng, Rui Wen Department of Radiation Oncology, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou People’s Hospital, Quzhou, Zhejiang, 324002, People’s Republic of ChinaCorrespondence: Zheng Peng; Rui Wen, Email hdpz@163.com; wenr@ucas.ac.cnBackground: Spider silk protein is a biocompatible and biodegradable protein that can self-assemble into various morphological materials for biomedical applications including drug delivery carriers. Spiders can spin up to seven types of silk fibers, each containing multiple silk proteins. Despite the numerous potential applications of these silk proteins, comprehensive and in-depth research on their specific roles and efficacy in drug delivery has yet to be conducted. The authors designed three new bioengineered spider silk proteins (M4R2, M4R4, and M4R6) and examined its property as a carrier of polypeptided drugs.Materials and Methods: To obtain the M4R2, M4R4, and M4R6 proteins, three constructs comprising 2, 4, and 6 repeat units of Araneus ventricosus major ampullate spidroin 4 (MaSp4) were engineered for prokaryotic expression using the Escherichia coli expression system. The particles made of M4R2, M4R4, and M4R6 silks were produced using a high concentration of potassium phosphate buffer. The physical properties of these particles were characterized by scanning electron microscopy (SEM) and zeta potential analysis. The cytotoxicity of particles was analyzed using MTT assay. The loading and release profiles of drugs were examined spectrophotometrically.Results: The three bioengineered silk proteins, M4R2, M4R4, and M4R6, were constructed, produced, and purified. These proteins exhibit self-assembly properties and formed particles. Furthermore, the these particles were not cytotoxic and had similar particle sizes but differed in loading efficiency and drug release rate. The loading of drugs into the M4R2 particles was more efficient (> 95%) than that into the M4R4 and M4R6 particles. In addition, the continuous release of ChMAP-28 from M4R2 particles over 30 days indicates its potential as a sustained-release carrier for positively charged peptide drugs. The high stability, excellent loading efficiency, and sustained-release performance of M4R2 particles make them an ideal choice for the delivery of positively charged peptide drugs.Conclusion: We developed three recombinant silk proteins, M4R2, M4R4, and M4R6, demonstrating that M4R2 particles, with stable colloidal properties, high loading efficiency of positively charged drugs, and controlled release rates, are promising new particulate drug carrier systems for the delivery of polypeptided drugs. Keywords: spider silk, particles, drug delivery, polypeptided drugs